2008
DOI: 10.1042/bj20071195
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide-mediated modulation of calcium/calmodulin-dependent protein kinase II

Abstract: The mechanisms of NO inhibition of CaMK [Ca(2+)/CaM (calmodulin)-dependent protein kinase] II activity were studied. In rat pituitary tumour GH3 cells, TRH [thyrotrophin (TSH)-releasing hormone]-stimulated phosphorylation of nNOS [neuronal NOS (NO synthase)] at Ser(847) was sensitive to an inhibitor of CaMKs, KN-93, and was enhanced by inhibition of nNOS with 7NI (7-nitroindazole). Enzyme activity of CaMKII following in situ treatment with 7NI was also increased. The in vitro activity of CaMKII was inhibited b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 53 publications
0
35
0
Order By: Relevance
“…3E). Although the effect of nNOS and NO on GluA1-S831 phosphorylation might be the result of effects on PKC or CaMKII, this possibility is unlikely because S-nitrosylation of these two enzymes reduces their activity (19)(20)(21). Also, a role for guanylate cyclase in mediating the activating effects of NO on GluA1-S831 phosphorylation is unlikely because inhibition of cyclic guanylate kinase increases glycine-stimulated phosphorylation of GluA1-S831 (22).…”
Section: Resultsmentioning
confidence: 99%
“…3E). Although the effect of nNOS and NO on GluA1-S831 phosphorylation might be the result of effects on PKC or CaMKII, this possibility is unlikely because S-nitrosylation of these two enzymes reduces their activity (19)(20)(21). Also, a role for guanylate cyclase in mediating the activating effects of NO on GluA1-S831 phosphorylation is unlikely because inhibition of cyclic guanylate kinase increases glycine-stimulated phosphorylation of GluA1-S831 (22).…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, it is noteworthy that excitatory glutamatergic neurotransmission reduces Cdk5 activity through enhancing the proteasome-dependent degradation of p35 (Wei et al, 2005). Interestingly, glutamate stimulation of neurons is able to trigger neuronal nitric oxide synthase activation, and results in protein S-nitrosylation (Bredt and Snyder, 1994;Song et al, 2008), making glutamate a likely candidate that can inhibit Cdk5 activity through S-nitrosylation. Thus, it is possible that S-nitrosylation of Cdk5 also contributes, at least in part, to the reduced kinase activity upon glutamate-induced NMDA receptor activation.…”
Section: Discussionmentioning
confidence: 99%
“…Under dynamic regulation by the NO signaling pathway, S-nitrosylation of a protein can modify its activity or function. For example, it has been reported that S-nitrosylation is important for regulating the catalytic activity of various kinases, including G protein-coupled receptor kinase 2, Akt/protein kinase B, Src kinase, inhibitory B kinase, or Ca 2ϩ /calmodulin-dependent protein kinase II (Reynaert et al, 2004;Yasukawa et al, 2005;Whalen et al, 2007;Song et al, 2008;Rahman et al, 2010). Whereas NO signaling pathway is one of the key regulators in a wide array of neurodevelopmental processes, including neuronal differentiation, neuronal survival, and synaptic plasticity (Guix et al, 2005), deregulation of this pathway has been implicated in the pathogenesis of neurological disorders such as Alzheimer's disease, Parkinson's disease, and stroke (Chung, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…A previous study showed that NO inhibits CaMKII activity through S-nitrosylation at C6 (30). To address this apparently conflicting finding, CaMKII was exposed to NO for varying periods of time (Fig.…”
Section: Prolonged Exposure To Nitric Oxide Reduces Camkii Activity-mentioning
confidence: 99%